Stahl's essential psychopharmacology : neuroscientific basis and practical applications - Stahl, Stephen M., 1951- (Cambridge, United Kingdom ; New York : Cambridge University Press, 2021)
"For this 5th edition of Stahl's Essential Psychopharmacology you will notice that every figure in the book has been revised, refreshed and updated with new colors, shading and outlining. About half the figures are entirely new. The number of chapters has decreased by one, with merger of mood stabilizers into treatments for mood disorders; the text itself and the total number of figures and tables are all approximately the same in length and number, although all chapters have been edited, most of them extensively with the details of what has changed listed below. The number of references has now been doubled. Overall, 14 drugs have new uses and indications presented, and 18 brand new drugs are introduced and discussed"--
Includes bibliographical references and index.
Keywords: Psykofarmaka; Psychopharmacology; Mental illness -- Chemotherapy; Psychopharmacology; MEDICAL / Mental Health; Psychopharmacology; Mental illness -- Chemotherapy; Psychotropic drugs